2009
DOI: 10.1073/pnas.0910887106
|View full text |Cite|
|
Sign up to set email alerts
|

Intramolecular amide bonds stabilize pili on the surface of bacilli

Abstract: Gram-positive bacteria elaborate pili and do so without the participation of folding chaperones or disulfide bond catalysts. Sortases, enzymes that cut pilin precursors, form covalent bonds that link pilin subunits and assemble pili on the bacterial surface. We determined the x-ray structure of BcpA, the major pilin subunit of Bacillus cereus . The BcpA precursor encompasses 2 Ig folds (CNA 2 and CNA 3 ) and one jelly-roll domain (XNA) eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 33 publications
3
84
0
Order By: Relevance
“…Furthermore, they carry intramolecular isopeptide bonds, which represent the Gram-positive counterparts of disulfide bonds found in Gram-negative bacterial pili. Isopeptide bonds are the result of an autocatalytic reaction that renders pili extremely resistant to proteolysis and high temperatures (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they carry intramolecular isopeptide bonds, which represent the Gram-positive counterparts of disulfide bonds found in Gram-negative bacterial pili. Isopeptide bonds are the result of an autocatalytic reaction that renders pili extremely resistant to proteolysis and high temperatures (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…These structures are composed of subunits covalently linked by means of intermolecular isopeptide bonds (32,36,(51)(52)(53). Furthermore, intramolecular isopeptide bonds have been found in most pilus subunits characterized to date (9,(26)(27)(28). These bonds may play a critical role in maintaining pilus integrity in the face of severe mechanical and chemical stress while bound to host cells and thus may provide a functional mode of stabilization for cell surface proteins involved in host pathogenesis.…”
mentioning
confidence: 99%
“…18,39,40 The pilin motif Lys residue is involved in the intermolecular isopeptide bond, and the neighboring Asn residue participates in the N1 domain intramolecular/domain isopeptide bond. In a significant discovery, revealed that during the pilus polymerization, the intramolecular isopeptide bond in the N1 domain forms only after the major pilin precursor participates in Lys-Thr inter-molecular amide bond formation, 41 leading to a polymerized and stable pilus shaft.…”
Section: Major/backbone Pilinsmentioning
confidence: 99%
“…4(d)]. 18 Each domain contains an isopeptide bond, including the N1 domain, in which the isopeptide bond is shown to be formed during the pilus polymerization. The N2 and N4 domains have E-type isopeptide bonds, in trans and cis configurations, respectively, and the N3 domain has a D-type isopeptide bond in a cis configuration.…”
Section: Major/backbone Pilinsmentioning
confidence: 99%
See 1 more Smart Citation